Belgium v. Senegal – Limits of the Interpretation of the Convention against Torture - Filipović, Milica (Pravni zapisi, 2013)
The problem which existed between Belgium and Senegal regarding Senegal avoiding to judge or extradite former Chad president for massive crimes committed during the eight-year governance had an epilogue before the International Court of Justice (ICJ). Decision made by the ICJ in this dispute- Questions Relating to the Obligation to Prosecute or Extradite (Belgium v. Senegal) is very important from the prospective of few aspects. At the first place the ICJ proved once again that its judgments pushing the boundaries of international law. Consequently, the ICJ stressed the importance of respecting the principle stipulated by relevant international agreements, as in this case, the Convention against Torture. Furthemore, the judgement is the first in the history of the ICJ in which it found that a State had standing based on obligations erga omnes partes. This finding opened different questions and one of them is significantly enlargement of the number and types of cases that can be brought before the ICJ. Besides, the ICJ analized nature and meaning of the obligations laid down in article 7 of the Convention- prosecute or extradite. In their memorials Belgium and Senegal had different interpretation of the principle aut dedere aut judicare. The ICJ resolved the dispute and has held that Article 7 of the Convention requires the State concerned to submit the case to its competent authorities for the purpose of prosecution, irrespective of the existence of a prior request for the extradition of the suspect. However, if the State in whose territory the suspect is present has received a request for extradition in any of the cases envisaged in the provisions of the Convention, it can relieve itself of its obligation to prosecute by acceding to that request. It follows that the choice between extradition or submission for prosecution, pursuant to the Convention, does not mean that the two alternatives are to be given the same weight.